A review on effects of diethyl ether on cyclic variations in diesel engines - İsmet Sezer (MANAS: Journal of Engineering)
Diethyl ether (DEE) can be used in diesel engines as a fuel or fuel additive. The review study was compiled from the findings of several studies in this area. The diverse techniques are employed to mitigate the detrimental pollutants emitted by diesel engines. The first approach to reducing emissions involves altering the fuel system and engine design to improve combustion, but this is an expensive and time–consuming process. The utilization of various exhaust gas devices, such as a particle filter and catalytic converter, is necessary for the second way. However, the engine performance could be negatively impacted by these tools. Additionally, these exhaust devices increases the vehicle and maintain costs. The use of different alternative fuels or fuel additives is the third way that reduces emissions while improving engine performance. The particulate matter (PM), smoke, and nitrogen oxides (NOx) are the main environmental pollutants released by diesel engines into the atmosphere. The decreasing PM and NOx emissions at the same time is practically very difficult. The majority of researches indicate that using alternative fuels, such as natural gas, biogas, and biodiesel, or blending additives with conventional or alternative fuels, is the best way to reduce emissions. However, the characteristics of the fuel have a significant influence on cycle variations, which have a significant impact on engine performance, fuel economy, and emissions. Therefore, it is very important that the results of studies on the impact of DEE on cyclic variation are evaluated together to practice applications and to guide future studies. As a result, the primary focus of this study is on the usage of DEE as a fuel or fuel additive with different diesel engine fuels. The aim of this review is to investigate, using the available knowledge in literature, how DEE affects cyclic variations.